2002
DOI: 10.1124/mol.62.3.521
|View full text |Cite
|
Sign up to set email alerts
|

A Fusion Protein of the Human P2Y1 Receptor and NTPDase1 Exhibits Functional Activities of the Native Receptor and Ectoenzyme and Reduced Signaling Responses to Endogenously Released Nucleotides

Abstract: To begin to address the functional interactions between constitutively released nucleotides, ectonucleotidase activity, and P2Y receptor-promoted signaling responses, we engineered the human P2Y 1 receptor in a fusion protein with a member of the ectonucleoside triphosphate diphosphohydrolase family, NTPDase1. Membranes prepared from Chinese hamster ovary (CHO)-K1 cells stably expressing either wild-type NTPDase1 or the P2Y 1 receptor-NTPDase1 fusion protein exhibited nucleotide-hydrolytic activities that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The inhibitory action of NTPDase1 was similar irrespective of whether the ectoenzyme was coexpressed on the same cell as the P2Y 1 receptor or was expressed on a different cell in cocultures with P2Y 1 receptor-expressing cells. Similar results were observed previously with a fusion protein of the human P2Y 1 receptor and NTPDase1 (Alvarado-Castillo et al, 2002). Addition of ATP or ADP to the bulk medium in these experiments may approximate the physiological situation in which activating nucleotide is released from a distant cell.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The inhibitory action of NTPDase1 was similar irrespective of whether the ectoenzyme was coexpressed on the same cell as the P2Y 1 receptor or was expressed on a different cell in cocultures with P2Y 1 receptor-expressing cells. Similar results were observed previously with a fusion protein of the human P2Y 1 receptor and NTPDase1 (Alvarado-Castillo et al, 2002). Addition of ATP or ADP to the bulk medium in these experiments may approximate the physiological situation in which activating nucleotide is released from a distant cell.…”
Section: Discussionsupporting
confidence: 85%
“…Heterologous expression of P2Y receptors has been widely reported to result in elevation of "basal" [ 3 H]inositol phosphate accumulation (Filtz et al, 1994;Parr et al, 1994;Lazarowski et al, 1995;Alvarado-Castillo et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…Using FRET microscopy of heterologously expressed fluorescence-tagged proteins, close molecular interaction, indicating complex formation, was observed between rat NTPDase1 and NTPDase2 and between NTPDase1 and a variety of P2Y nucleotide and P1 adenosine receptors [164]. The close interaction between NTPDases and P2Y receptors would have a severe impact on the availability of nucleotide agonists at their receptor, as has been implicated from the analysis of an NTPDase1/P2Y 1 receptor fusion protein [165].…”
Section: Protein Interactionsmentioning
confidence: 91%
“…Because of the location of NTPDase1 on endothelial cells and its ability to hydrolyze ADP, a ligand of the P2Y1 receptor that promotes platelet aggregation, its important role in thromoboregulation was immediately recognized. Many in vitro studies followed that showed (1) an inverse correlation of NTPDase1 activity with platelet aggregation [28,66,67], (2) a decrease of NTPDase1 activity upon endothelial cell activation [67], and (3) attenuation of ATP signaling in cells expressing an NTPDase1-P2Y1 receptor fusion protein [68]. The last study demonstrated the importance of NTPDase1 in regulating purinergic signaling.…”
Section: Cr3 Acr3mentioning
confidence: 99%